Managing curriculum and assessment a practitioner's guide - Nichols, Beverly W.; Shidaker, Sue; Johnson, Gene; Singer, Kevin (Gale virtual reference library, 2006)
This guide provides the basic elements of a curriculum management system that will help school districts address, in a practical manner, the need to improve student learning.